Earthworm consumption as a source of protein around the world: A review - Rosa, Liciane Oliveira da; Souza, Karine Fonseca de; Burin, Paula; Trindade, Ketellen Nunes; Fick, Rubiane Buchweitz; Santos, Fabiana Fernandes dos; Mendes, Ana Clara Marins; Côrrea, Luciara Bilhalva; Côrrea, Érico Kunde; Dias, Álvaro Renato Guerra (Seven Editora, 2023)
Population growth will increase global food demand compared to current demand. This factor leads to a shift in consumption to a more diverse diet, which includes a larger share of processed foods, meats, dairy, and fish, all of which add pressure to the supply system. The introduction of more sustainable food sources, such as earthworms, will improve the health of the planet and humans. The purpose of this article is to analyze and present a comprehensive literature review on earthworm consumption in the world. A literature survey was conducted from May to July 2023. The works related to the theme were searched through research on scientific platforms over a period of 27 years. A total of 10 articles related to the theme were found, most of which were in Europe, followed by Asia and America. All studies highlighted the importance of exploring earthworms as a viable sustainable protein alternative for the future, and more studies and awareness of the benefits of their consumption are needed. DOI:https://doi.org/10.56238/interdiinovationscrese-026